Nuclear DUX4 immunohistochemistry is a highly sensitive and specific marker for the presence of CIC::DUX4 fusion in CIC-rearranged sarcomas: a study of 48 molecularly confirmed cases - Macedo, Rodrigo T; Baranovska-Andrigo, Vira; Pancsa, Tamás; Klubíčková, Natálie; Rubin, Brian P; Kilpatrick, Scott E; Goldblum, John R; Fritchie, Karen J; Billings, Steven D; Michal, Michal; Švajdler, Marián; Kinkor, Zdeněk; et al. (Histopathology, 2025)
AIMS: CIC-rearranged sarcomas (CRS) are clinically aggressive undifferentiated round cell sarcomas (URCS), commonly driven by CIC::DUX4. Due to the repetitive nature of DUX4 and the variability of the fusion breakpoints, CIC::DUX4 fusion may be missed by molecular testing. Immunohistochemical (IHC) stains have been studied as surrogates for the CIC::DUX4 fusion. We aim to assess the performance of DUX4 IHC in the work-up of CRS and its expression in non-CRS round cell or epithelioid neoplasms. METHODS AND RESULTS: Cases of molecularly confirmed CRS (n = 48) and non-CRS (n = 105) were included. CRS cases consisted of 35 females and 13 males, with ages ranging from less than 1 year to 67 years (median = 41 years). Among the molecularly confirmed non-CRS cases, C-terminal DUX4 expression was investigated in Ewing sarcomas (38 cases), alveolar rhabdomyosarcomas (18 cases), desmoplastic small round cell tumours (12 cases) and synovial sarcomas (n = five), as well as in non-mesenchymal neoplasms such as SMARCA4/SMARCB1-deficient tumours (n = five), carcinomas of unknown primary (n = three) and haematolymphoid neoplasms (four cases). DUX4 IHC was considered positive when strong nuclear expression was detected in more than 50% of neoplastic cells. When used as a surrogate for the diagnosis of CRS, the sensitivity and specificity of DUX4 IHC was 98 and 100%, respectively. Only one CRS case was negative for DUX4 IHC and harboured a CIC::FOXO4 fusion. CONCLUSIONS: DUX4 IHC is a highly sensitive and specific surrogate marker for the presence of CIC::DUX4 fusion, demonstrating its utility in establishing a diagnosis of CRS.
Keywords: Young Adult; Male; Child, Preschool; small round cell tumours; mladý dospělý; Adolescent; genová přestavba; Soft Tissue Neoplasms; Infant; Child; round cell sarcoma; dítě; Adult; Aged; dospělí; imunohistochemie; mužské pohlaví; senioři; fúzní onkogenní proteiny; sarkom; mladiství; CIC‐rearranged sarcomas; předškolní dítě; Oncogene Proteins, Fusion; CIC::DUX4; lidé; ženské pohlaví; Immunohistochemistry; Biomarkers, Tumor; Gene Rearrangement; Humans; Sensitivity and Specificity; kojenec; senzitivita a specificita; nádory měkkých tkání; Sarcoma; Homeodomain Proteins; Female; immunohistochemistry; lidé středního věku; homeodoménové proteiny; nádorové biomarkery; Middle Aged